Experimental Evaluation of Concrete Mixes with Alccofine-1203 and Fly Ash Additions (International Journal of Scientific Research in Science and Technology, 2024)
The production of cement significantly contributes to carbon dioxide emissions, exacerbating global warming. To mitigate this issue, the exploration of alternative materials that can partially or fully replace cement in concrete is crucial. This study focuses on Alccofine 1203, a high-reactivity, glass-rich material produced through controlled granulation. It aims to assess the impact of incorporating Alccofine 1203 as a partial replacement for cement on the performance of concrete. In this experiment, Alccofine was substituted for cement at varying replacement levels of 0%, 10%, 15%, 20%, and 25%. Concrete samples of grade M30 were tested for workability using slump cone and compaction factor tests, as well as for compressive strength and split tensile strength at 7 and 28 days of curing. The results indicate a notable improvement in concrete strength with Alccofine replacement, achieving optimal performance at a 25% replacement level. Beyond this threshold, a decline in strength was observed. These findings suggest that Alccofine 1203 can significantly enhance concrete performance and offer a viable option for reducing cement’s carbon footprint, promoting the use of sustainable materials in construction.